Both tumor depth and diameter are predictive of sentinel lymph node status and survival in Merkel cell carcinoma. Issue 18 (2nd June 2015) - Smith, Franz O.; Yue, Binglin; Marzban, Suroosh S.; Walls, Brooke L.; Carr, Michael; Jackson, Ryan S.; Puleo, Christopher A.; Padhya, Tapan; Cruse, C. Wayne; Gonzalez, Ricardo J.; Sarnaik, Amod A.; Schell, Michael J.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The purposes of this study were 1) to determine the impact of primary tumor‐related factors on the prediction of the sentinel lymph node (SLN) status and 2) to identify clinical and pathologic factors associated with survival in Merkel cell carcinoma (MCC). METHODS An institutional review board–approved, retrospective review of patients with MCC treated between 1988 and 2011 at a single center was performed. Patients were categorized into 5 groups: 1) negative SLN, 2) positive SLN, 3) clinically node‐negative but SLN biopsy not performed, 4) regional nodal disease without a known primary tumor, and 5) primary MCC with synchronous clinically evident regional nodal disease. Factors predictive of the SLN status were analyzed with logistic regressions, and overall survival (OS) and disease‐specific survival (DSS) were analyzed with Cox models and competing risk models assuming proportional hazards, respectively. RESULTS Three hundred seventy‐five patients were analyzed, and 70% were male; the median age was 75 years. The median tumor diameter was 1.5 cm (range, 0.2‐12.5 cm), and the median tumor depth was 4.8 mm (range, 0.3‐45.0 mm). One hundred ninety‐one patients underwent SLN biopsy, and 59 (31%) were SLN‐positive. Increasing primary tumor diameter and increasing tumor depth were associated with SLN positivity (P = .007 and P = .017, respectively). Age and sex were not associated with the SLN status. Immunosuppression, increasing tumor diameter, and increasing tumor depth were associated with worse OS (P = .007, P = .003, and P = .025, respectively). DSS differed significantly by group and was best for patients with a negative SLN and worst for those with primary MCC and synchronous clinically evident nodal disease (P = .018). CONCLUSION For patients with MCC, increasing primary tumor diameter and increasing tumor depth are independently predictive of a positive SLN, worse OS, and worse DSS. Tumor depth should be routinely reported when primary MCC specimens are being evaluated histopathologically. Cancer 2015;121:3252–3260. © 2015 American Cancer Society.